PENERAPAN STRATEGI DIGITAL MARKETING MELALUI INFUENCER PADA UMKM BURGOUTH DI GEGERKALONG BANDUNG - Raden Mochamad Raka Boedianto; Ady Tia Ramadhan (Yayasan Insani Mandiri Santani, 2025)
This study explores the effectiveness of digital marketing strategies and the role of influencers in increasing product sales for small businesses in the context, using the local fast-food brand